Pemaknaan Mitigasi Kutural Dan Struktural Masyarakat Lereng Selatan Gunung Api Merapi - Purnomo, Nugroho Hari; Hariyono, Widodo (Jurnal Tata Kota dan Daerah, 2014)
Since 1960's the government of Indonesia has intensively built structural mitigation infrastructure on the slopes of Merapi before it erupted in 2010. In the other hand, the community has been introduced cultural mitigation inherited by their ancestors. The problem is the way how they understand both mitigation models.This study aims to determine people's interpretation towards cultural and structural mitigation before and after the eruption of Merapi volcano in 2010. The study used in-depth interviews method to victims of Merapi eruption in 2010, who live in disaster prone areas (KRB) II and III on the southern slope of Kepuharjo and Umbulharjo village, Cangkringan, Sleman, Yogyakarta. The hermeneutic analysis is applied to interpretative ideas associated with an analog understood from the oral and textual data. The analysis is supported by the historical literature, which gives an overview of Merapi for its community in the past.The study results that people’s interpretation of cultural and structural mitigation in Merapi society can be divided into two based on time before and after its eruption in 2010. The first groups or ones with ideas before the eruption, cultural mitigation is more meaningful for them and after eruption they combine it as an integrated cultural and structural mitigation. While the second community, before and after eruption, they have already made sense of integrated cultural and structural mitigation. In cultural mitigation, in interacting with nature, they understand about the fate of life that comes from the Javanese philosophy and beliefs of the Merapi volcano. In structural mitigation, the government constructs people to make sense that based on scientific rationality their life with nature on the slopes of Merapi volcano can emerge a risk of disaster anytime.Keywords: interpretation, mitigation, cultural, structural.